„Sacra à Deo in corde discenda, natura ex natura." Die Observationes Johann Christian Senckenbergs als medico‐theologische Aufzeichnungspraktik. Issue 3 (1st September 2017) - Faßhauer, Vera
Abstract: "Sacra à Deo in corde discenda, natura ex natura." Johann Christian Senckenberg's Observationes as a Medico‐Theological Writing Method . In his early diaries, the pietist physician Johann Christian Senckenberg has taken down large amounts of observation data which mostly concentrated on his own body and soul. Earlier research has mistaken his diligent self‐observation for hypochondria and unworldliness, especially since the author had never endeavoured to analyze and publish his work. The article shows that both his writing practice and his reluctance to process and share its results are due to his deeply religious and firmly anti‐rationalist conviction. The main purpose of his journal keeping was the attainment of religious self‐knowledge and professional self‐perfection. Scientific publications he considered to be hypothetical and dogmatic, be it in theology or medicine; moreover, their authors were often enough driven by their self‐love and desire for fame. In his eyes, the only godly way of knowledge acquisition was the humble, diligent and minute study of divine creation according to the Hippocratic method. The most immediate and reliable way of achieving true wisdom, however, was the observation of God's work within one's own body and mind, which were subject to the effects of God's grace and punishment as well as to atmospheric, environmental and dietetic circumstances.